#Ragazzemondiali: Spinte globalizzanti e specificità nazionali nel calcio femminile italiano (Glocalism: Journal of Culture, Politics and Innovation, 2020)
Thanks to the stunning performance of the Italian national team (who reached the quarter-finals of the FIFA Women’s World Cup in France), the summer of 2019 was the apex in the development of women’s football in Italy: it was greatly helped by its integration into the huge FIFA system (including sponsors and media). This essay tries to investigate the quality and quantity of this external, global influence. Gender, geographic, and historical filters will be used to gain a better understanding of the phenomenon. The analysis will be based mainly on sports blogs, online newspapers, interviews with footballers and supporters’ tweets, in order to capture the most realistic view of the sociological reality of the Italian women’s football movement. The globalizing tendencies, models (a new image of women in sport) and values (such as female empowerment and diversity) shaped the representation of Italy’s national team as broadcasted by media to the Italian audience, unaccustomed to viewing young women playing soccer. On the other hand, the Italian female footballers, who took advantage of the global influence in order to improve their condition, were successful in shaping it (for example, by showing an image of the hard-headed footballer, rather than the arrogant one coming from the USA). What happened in Italy during the summer of 2019 seems like an interesting (and successful) case of glocalization in women’s sports, played out in such a gendered context as the Italian one.
Keywords: gender studies; globalization; sport; women’s football; female empowerment